2013
DOI: 10.1038/ncomms3210
|View full text |Cite
|
Sign up to set email alerts
|

Concentration memory-dependent synaptic plasticity of a taste circuit regulates salt concentration chemotaxis in Caenorhabditis elegans

Abstract: It is poorly understood how sensory systems memorize the intensity of sensory stimulus, compare it with a newly sensed stimulus, and regulate the orientation behaviour based on the memory. Here we report that Caenorhabditis elegans memorizes the environmental salt concentration during cultivation and exhibits a strong behavioural preference for this concentration. The right-sided amphid gustatory neuron known as ASER, senses decreases in salt concentration, and this information is transmitted to the postsynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
228
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(238 citation statements)
references
References 46 publications
10
228
0
Order By: Relevance
“…Thus, cultivating animals at high CO 2 results in a drive toward higher CO 2 levels rather than a preference for their previous cultivation condition. This is in contrast to other sensory behaviors in C. elegans , including salt chemotaxis and thermotaxis, where animals are attracted to their prior cultivation condition [17, 18]. Animals raised at high CO 2 were not attracted to 40% CO 2 in the 2.5%−40% CO 2 gradient (Figure S1D), suggesting that they retain the ability to avoid toxic levels of CO 2 [19].…”
Section: Resultsmentioning
confidence: 85%
“…Thus, cultivating animals at high CO 2 results in a drive toward higher CO 2 levels rather than a preference for their previous cultivation condition. This is in contrast to other sensory behaviors in C. elegans , including salt chemotaxis and thermotaxis, where animals are attracted to their prior cultivation condition [17, 18]. Animals raised at high CO 2 were not attracted to 40% CO 2 in the 2.5%−40% CO 2 gradient (Figure S1D), suggesting that they retain the ability to avoid toxic levels of CO 2 [19].…”
Section: Resultsmentioning
confidence: 85%
“…PKD activation is required for TFEB nuclear translocation, and downstream transcription of host defense genes. Recent evidence supports a role for PLC-1 downstream of EGL-30 for salt chemotaxis as well (Kunitomo et al, 2013). We observed a complex phenotype for knockdown of plc-1 .…”
Section: Discussionmentioning
confidence: 82%
“…Using this approach, it was shown that ASH photoactivation triggers withdrawal behaviours mimicking the endogenous response [50,59]. The strength of the optogenetic activation of the ASH neurons directly correlated with the magnitude of the behavioural response [50,60].…”
Section: Sensory Systemsmentioning
confidence: 99%